Nilai-Nilai Pendidikan Hindu Dalam Yajña Sesa di Kecamatan Basarang Kabupaten Kapuas - Riyade, Wayan Oka; Karya, I Wayan; Sigai, Ervantia Restulita L (Satya Widya: Jurnal Studi Agama, 2023)
Yajña Sesa is the simplest food offering consisting of rice, side dishes (cooked) as symbol of gratitude to Ida Sang Hyang Widhi Wasa/God Almighty. In fact, there is a lack understanding of some people related to the form of implementation, functions and values ​​of Yajña Sesa. The theories used in this study are the theory of symbols, structural functional theory and value theory. The research method used is a qualitative method. The types of data sources are primary and secondary data sources. This study used purposive sampling and data collection techniques with observation, interviews and document study.